Fabrication and characterization of aluminum nitride thick film coated on aluminum substrate for heat dissipation. Issue 16 (December 2016) - Hahn, Byung-Dong; Kim, Yuna; Ahn, Cheol-Woo; Choi, Jong-Jin; Ryu, Jungho; Kim, Jong-Woo; Yoon, Woon-Ha; Park, Dong-Soo; Yoon, Seog-Young; Ma, Byungjin
Abstract: For effective heat dissipation in high-power LED applications, aluminum nitride (AlN) thick films as thermally conductive dielectric layers were developed, which were deposited on an Al substrate by aerosol deposition (AD). The aerosol-deposited AlN thick films on Al substrates have advantages over conventional polymer-based dielectric substrates or ceramic substrate mounted heatsink systems including an epoxy adhesive, such as excellent heat dissipation capacity and low thermal resistance. AD is an effective method to fabricate high-quality AlN thick film without the Al2 O3 phase because the film is formed at room temperature. Highly dense and well-adhered, pure AlN thick films with thicknesses up to 30 µm were deposited on an Al substrate. AlN-Al2 O3 and AlN-polyvinylidene fluoride (PVDF) composite films were also deposited on an Al substrate in order to investigate the effect of Al2 O3 and polymer on the microstructure and thermal properties. Among the films, pure AlN thick film exhibited the highest dielectric strength, the highest thermal conductivity, and the lowest thermal resistance. Therefore, it can be expected that the aerosol-deposited AlN thick film on Al substrate could be used as a powerful heatsink.